Prevalence of oral changes in patients with special needs (Research, Society and Development, 2020)
The aim of this study is to identify the prevalence of oral changes in patients seen at the Special Needs Patients’ Clinic of the Dentistry School, UEPB, in the city of Araruna, PB. A retrospective, observational and quantitative study was carried out with the analysis of 59 medical records of patients with special needs seen between the semesters of 2015.2 and 2017.1, since the implementation of this service. Data on the sex, age, CPO-D index, dental treatments and duration of treatment were recorded. Data collection was taken through a secondary form using google forms to store the necessary information and then proceed the study. Data were organized and exported to Microsoft Excel 2016 and then SPSS program was used to analyze statistically and categorize them. It was observed that males were more prevalent (50.2%) in relation to females (48.2%). Age group was composed mostly (76.3%) by people under 40 years. The oral changes were cavities, in 69.7% of patients, periodontal disease in 57.6% and other lesions, such as actinic cheilitis, in 7.6%. The CPO-D index average was 12.10; the dental procedures more performed were restorations (84.75%), supra / subgengival scraping (57.62%), extractions (20.03%), topical application of fluoride (44.06%) and prosthetic rehabilitation (1.69%). Out of 59 patients 74.57% presented periodontal disease and cavities as the main oral changes. The highest incidence of cavities was in females (82.8%) and periodontal disease in males (70.0%).